Overweight: atherogenesis risk marker in children between 8 and 9 years - Beatriz Sabina Roméu; Margarita Rosa Romeu Escobar; Juan José Apolinaire Pennini (Medisur, 2008)
Background: Many significant health problems hold the attention of pediatricians, and even when there is an increased interest on premature atherosclerosis risk factors, it is still a field to be studied. Objectives: To determine differences in the emergence of atherogenesis risk factors in children between 8 and 9 years with normal weight and overweight. Methods: Analytic research, with case control design, developed in three primary schools belonging to the Clinic “Dr. Cecilio Ruiz de Zarate” in Cienfuegos. A group with overweight or obese children was formed and another control group selected by randomized simple sampling with normal weight children. Measurements of weight, height, waist circumference and blood pressure were performed. Parents were surveyed for data about children and family history. In overweight children, glucose and triglycerides were measured. To validate results, Chi-Squared test was used. To compare measurements, Mathn Whitney test was employed. Results: Overweight and obesity were associated with: male sex, with people, sedentary patients, and prenatal antecedents of overweight. 78% of overweight children had values of blood pressure higher than 90 percentile for their sex and height, contrasting with the 26% in normal weight children. Six children were diagnosed with metabolic syndrome.